2016
DOI: 10.1108/md-11-2014-0651
|View full text |Cite
|
Sign up to set email alerts
|

CEO transformational and transactional leadership and organizational innovation

Abstract: Purpose – Organizational innovation is critical for firm competitive advantage. Yet, we do not know enough about the relationship between leadership and organizational innovation. The purpose of this paper is to examine the influence of chief executive officer (CEO) transformational and transactional leadership on organizational innovation. The authors examine the moderating role of environmental dynamism. Design/methodology/approach – T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 99 publications
4
157
1
2
Order By: Relevance
“…For example, previous studies on FLEs' creativity have shown that managerial feedback enhances the positive effect of employee's creativity on sales quota obtainment (Agnihotri et al, ), while others show outcome rewards intensify the effect of organizational customer orientation on product radical innovation (Joshi, ). While the literature supports the positive effects of TRL on employee performance (Prasad and Junni, ), some studies report negative effects from TRL style on employees behavior (Pieterse et al, 2010). Such results have led some researchers to believe that leadership style is not a direct input into employee behavior but is rather a contingency factor (O'Cass and Sok, ; Schmitz, Lee, and Lilien, ).…”
Section: Literature Review: Conceptual Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, previous studies on FLEs' creativity have shown that managerial feedback enhances the positive effect of employee's creativity on sales quota obtainment (Agnihotri et al, ), while others show outcome rewards intensify the effect of organizational customer orientation on product radical innovation (Joshi, ). While the literature supports the positive effects of TRL on employee performance (Prasad and Junni, ), some studies report negative effects from TRL style on employees behavior (Pieterse et al, 2010). Such results have led some researchers to believe that leadership style is not a direct input into employee behavior but is rather a contingency factor (O'Cass and Sok, ; Schmitz, Lee, and Lilien, ).…”
Section: Literature Review: Conceptual Backgroundmentioning
confidence: 98%
“…Previous studies have shown that transactional leaders can elevate the effect of FLEs' behaviors on their performance because they lead by providing concrete directions, specify clear expectations, and provide instructions on how to complete tasks to achieve desired outcomes (Pieterse et al, ; Prasad and Junni, ; Schmitz et al, ; Sok and O'Cass, ). However, in KIBS firms leaders using very high levels of TRL may not necessarily achieve similar outcomes as those who use low or moderate levels of TRL.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Their leadership is rooted in some values, such as morality, justice, organizational commitment, innovation, integrity, and commitment to excellence. Even though their image is not that of gifted individuals, they are conscious that inspiring, motivating, and considering people is vital in any leadership process (Prasad & Junni, 2016). Perhaps, charisma, in this case, can be described as conscious (Avolio and Yammarino, 2002) because leaders tend to take their job too seriously and this behavior may cause negative reactions in their followers.…”
Section: Identifying Gaps Between the Current Leader And The Future Lmentioning
confidence: 99%
“…The leader of the future, too, must be able to combine different forms of charisma -"idealized influence, inspirational leadership, and intellectual stimulation, individual consideration" - (Prasad & Junni, 2016, p. 1542, power and participation. Likewise, this leader should be able to use coercion, reward, legitimacy, expertise, reference, position power, and personal power.…”
Section: Identifying Gaps Between the Current Leader And The Future Lmentioning
confidence: 99%
“…A liderança transformacional influencia a gestão de pessoas de diferentes modos, tais como: alavancando a identificação dos colaboradores com a firma (Behery, 2016), configurando um clima social adequado ao comprometimento, criatividade e inovação (Bai, Li, & Xi, 2012;Chang, 2016;Khalili, & Khalili, 2016;Mittal, & Dhar, 2015;Prasad, & Junni, 2016;Raj, & Srivastava, 2017;Sarros, Cooper, & Santora, 2008;Sattayaraksa, & Boon-itt, 2016), promovendo a ambidestria organizacional (Chang, 2015) (Collins et al, 2004;Collins, 2007).…”
Section: Estilo De Liderança Do Empreendedor E Fatores De Atraçãounclassified